Conjugated anionic PEG-citrate G2 dendrimer with multi-epitopic HIV-1 vaccine candidate enhance the cellular immune responses in mice. (17th November 2017) - Abdoli, Asghar; Radmehr, Nina; Bolhassani, Azam; Eidi, Akram; Mehrbod, Parvaneh; Motevalli, Fatemeh; Kianmehr, Zahra; Chiani, Mohsen; Mahdavi, Mehdi; Yazdani, Shaghayegh; Ardestani, Mehdi Shafiee; Kandi, Mohammad Reza; et al.
Abstract: Multi-epitope vaccines might cause immunity against multiple antigenic targets. Four immunodominant epitopes of HIV-1 genome were used to construct a polytope vaccine, formulated by dendrimer. Two regimens of polytopes mixture with dendrimer were utilized to immunize BALB/c mice. Adjuvants were also used to boost immune responses. The conjugated polytope could arouse significant cellular immune responses ( P  < 0.05) and Th1 response showed higher intensity compared to Th2 ( P  < 0.05). Our study depicted that conjugated dendrimer with multi-epitopic rHIVtop4 would efficiently induce cell-mediated immune responses and might be considered as promising delivery system for vaccines formulation.